A novel single-crystal L12-strengthened Co-rich high-entropy alloy with excellent high-temperature strength and antioxidant property - W.C. Xiao; S.F. Liu; Y.L. Zhao; J.J. Kai; X.J. Liu; T. Yang (Journal of Materials Research and Technology, 2023)
Severe intermediate-temperature embrittlement as well as rapid softening and oxidation at high temperatures are significant problems for high-entropy alloys (HEAs) in polycrystalline structures, which greatly limit their applications in modern industries. In this study, a novel Co-rich single-crystal high-entropy alloy (HEA), Co41Ni35Al11·5Ta2·5Cr4Ti6 (at.%), was innovatively developed. After isothermally aged at 1250 °C, this alloy exhibits an ultrahigh volume fraction of cuboidal L12-type nanoprecipitates (∼80%) which is higher than those of previous Co-based superalloys. More importantly, the present HEA shows excellent mechanical performance at both ambient and elevated temperatures, and no intermediate temperature embrittlement and rapid softening were observed. Noticeably, the yield strength can still maintain at ∼800 and ∼500 MPa when tested at 900 and 1000 °C, which are superior to other conventional single-crystal alloys. Moreover, extraordinary oxidation resistance can be achieved at the high temperature of 1000 °C due to the formation of a compact sandwich-structured oxide layer.